Monolithic photocatalytic board and preparation method and application thereof
Patent Information
- Application Number
- CN202611181283.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
然而,现有负载方法多采用物理涂覆、粘结剂粘附或简单热处理方式,催化剂与基底之间主要为物理附着或弱相互作用,在流体冲刷、超声或长期运行条件下容易发生脱落,导致催化剂稳定性差、使用寿命短,仍然难以满足连续流反应系统的使用要求
[0043]进一步优选地,所述流体驱动装置的流量为50mL/min~200mL/min。
Smart Images

Figure CN122999252A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalytic materials and photocatalytic reaction engineering technology, specifically to an integral photocatalytic plate, its preparation method, and its application. Background Technology
[0002] Hydrogen peroxide (H2O2) is an important green oxidant widely used in chemical synthesis, medical disinfection, environmental pollution control, and energy chemistry. Currently, industrial hydrogen peroxide is mainly produced centrally via the anthraquinone process. However, this process involves multiple hydrogenation and oxidation reactions, requiring large-scale separation and extraction equipment. The overall process is complex and energy-intensive. Furthermore, high-concentration hydrogen peroxide solutions pose safety hazards during storage and transportation, limiting its application in decentralized, on-demand supply scenarios.
[0003] In recent years, hydrogen peroxide synthesis technology based on semiconductor photocatalysis has received widespread attention due to its unique advantages. This technology uses light energy to excite a catalyst to generate photogenerated electrons and holes, which then drive the two-electron reduction reaction (ORR) of dissolved oxygen or the water oxidation reaction (WOR) to produce hydrogen peroxide at room temperature and pressure. The entire process uses water and oxygen as raw materials and light energy as the energy source, without involving organic solvents or high-pressure hydrogen, and has good process safety and environmental compatibility, and is considered a promising green preparation route.
[0004] Currently, most existing photocatalytic hydrogen peroxide synthesis systems employ powdered photocatalysts, such as graphitic carbon nitride (g-C3N4), titanium dioxide (TiO2), and zinc oxide (ZnO). These powdered catalysts exhibit good initial reaction rates in reactors due to their high specific surface area and abundant surface active sites. However, in practical engineering applications, powdered photocatalytic systems have many inherent limitations. First, under flowing reaction conditions, nano- to micron-scale powdered catalysts are prone to agglomeration and sedimentation, leading to a decrease in effective reaction area and mass transfer efficiency. Second, the loss of powdered catalysts in continuous liquid systems is a significant problem, not only causing the loss of expensive catalytic materials but also potentially introducing particulate secondary pollutants, increasing the burden on subsequent water treatment. Furthermore, after the reaction, the powdered catalyst needs to be recovered through centrifugation or filtration, a complex process with low recovery rates, making continuous operation difficult. These problems collectively make it difficult for powdered photocatalytic systems to adapt to the commonly used fixed-bed or flow-through reactor configurations in industry, limiting the large-scale and engineering progress of photocatalytic hydrogen peroxide preparation technology.
[0005] To overcome the difficulty in recovering powdered catalysts, existing research has attempted to support photocatalytic active components on glass, ceramic, or metal substrates to form supported catalysts. However, current support methods mostly employ physical coating, binder adhesion, or simple heat treatment. The catalyst and substrate are primarily physically attached or weakly interact, making them prone to detachment under fluid erosion, ultrasonic conditions, or long-term operation. This results in poor catalyst stability and short service life, still failing to meet the requirements of continuous flow reaction systems.
[0006] Therefore, there is an urgent need to develop a novel monolithic photocatalytic functional material and its supporting reaction system, which can achieve a firm and durable bond between the catalytically active component and the supporting substrate, while taking into account both high photocatalytic activity and excellent hydrodynamic stability. It can operate in a flow system for a long time without separation and recovery, thus meeting the actual needs of continuous and large-scale photocatalytic hydrogen peroxide production processes. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide an integral photocatalytic plate, its preparation method, and its application.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides an integral photocatalytic plate, comprising an oxide substrate and a carbon nitride catalytic layer formed on the surface of the oxide substrate; The carbon nitride catalyst layer is connected to the oxide substrate through a MOPN interface covalent bridging structure, wherein M includes at least one of B, Sn, Al, Zr, Mg, Ti, and Si; The carbon nitride catalyst layer is formed by in-situ thermal polycondensation of nitrogen-containing organic precursors and phosphorus-containing compounds. The molar ratio of the nitrogen-containing organic precursor to the phosphorus-containing compound is (0.8~1.2):1.
[0009] The integral photocatalytic plate of the present invention anchors the carbon nitride catalyst layer to the surface of the oxide substrate by constructing a MOPN covalent bridging structure, forming an integral photocatalytic component with high interfacial bonding strength. The interfacial covalent bridging structure uses the P atom as the bridging center. One end of the P atom is bonded to the MO bond on the surface of the oxide substrate through the MOP bond, and the other end is covalently connected to the N atom in the carbon nitride catalyst layer through the PN bond. Thus, the catalyst layer is fixed to the substrate surface in the form of covalent bonds, forming an integral structure. This improves the defect of easy detachment of the catalyst layer in traditional physical coating or adhesive fixing methods, so that the photocatalytic plate can maintain the integrity and stability of the structure under harsh conditions such as high-speed fluid scouring and ultrasonic treatment.
[0010] Specifically, in the preparation process of the carbon nitride catalytic layer of the present invention, phosphorus-containing compounds serve as the interfacial bridging reaction source. While forming carbon nitride through thermal polymerization, they react with oxygen-containing groups and the carbon nitride skeleton on the substrate surface, thereby constructing a MOPN covalent connection structure in situ at the interface. This achieves a firm anchoring of the carbon nitride photocatalytic layer on the surface of the inorganic substrate. The resulting photocatalytic plate has excellent interfacial bonding strength, structural stability, and reusability. It can be directly used as an integral photocatalytic component in a continuous flow phase photocatalytic reaction system, achieving long-term stable operation without solid-liquid separation. It is suitable for fields such as photocatalytic preparation of hydrogen peroxide, degradation of organic pollutants, and antibacterial disinfection.
[0011] Through research, the inventors discovered that controlling the molar ratio of nitrogen-containing organic precursors and phosphorus-containing compounds within the aforementioned range is crucial for achieving a synergistic effect of high interfacial bonding strength and high photocatalytic activity in the preparation of the carbon nitride catalyst layer of this invention. When the proportion of phosphorus-containing compounds is too high, although interfacial bonding can still be formed, excessive phosphorus occupies active sites in the carbon nitride framework, leading to a decrease in light absorption capacity. Simultaneously, an excessively thick insulating POP oligomer layer forms at the interface, increasing interfacial resistance and hindering the interfacial transport of photogenerated electrons, ultimately resulting in a significant reduction in photocatalytic activity. Conversely, when the proportion of phosphorus-containing compounds is too low, a continuous and complete MOPN bridging network cannot be formed at the interface. The catalyst layer and substrate remain primarily physically attached, resulting in insufficient bonding strength. During the reaction, the catalyst layer is prone to peeling off, causing not only the loss of catalytic material but also making the exposed substrate interface a recombination center for photogenerated charge carriers, severely deteriorating catalytic performance.
[0012] The molar ratio of the nitrogen-containing organic precursor to the phosphorus-containing compound is one or both of the following: 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1.
[0013] In a preferred embodiment of the integral photocatalytic plate of the present invention, the oxide substrate is any one of alumina ceramic sheet, titanium dioxide ceramic sheet, silicon dioxide ceramic sheet, zirconium oxide ceramic sheet, FTO conductive glass, porous alumina ceramic, and alumina honeycomb ceramic.
[0014] Preferably, the oxide substrate is an alumina ceramic sheet.
[0015] In a preferred embodiment of the integral photocatalytic plate of the present invention, in the MOPN interface covalent bridging structure, the P atom serves as the bridging center, with one end chemically bonded to the surface of the oxide substrate via MOP bonds, and the other end chemically bonded to the carbon nitride catalyst layer via PN bonds.
[0016] One end of the MOPN interface covalent bridging structure of the present invention is bonded to the MO bond on the surface of the oxide substrate, and the other end is bonded to the nitrogen-containing structure in the carbon nitride framework, thereby anchoring the carbon nitride catalytic layer to the surface of the inorganic substrate through covalent bonds and forming an integral photocatalytic plate, thereby simultaneously achieving synergistic optimization of structural stability and photocatalytic activity.
[0017] In a preferred embodiment of the integral photocatalytic plate of the present invention, the nitrogen-containing organic precursor includes at least one of melamine, dicyandiamide, and thiourea.
[0018] The nitrogen-containing organic precursor used in the preparation of the carbon nitride catalyst layer of the present invention provides sufficient active sites for the reaction with phosphorus to form PN bonds, while ensuring the high light absorption coefficient and carrier mobility of the photocatalytic layer.
[0019] Preferably, the nitrogen-containing organic precursor includes melamine.
[0020] In a preferred embodiment of the integral photocatalytic plate of the present invention, the phosphorus-containing compound includes at least one of phosphoric acid, phosphate, and organophosphorus compounds.
[0021] Preferably, the phosphorus-containing compound includes phosphoric acid.
[0022] Secondly, the present invention provides a method for preparing the integral photocatalytic plate, comprising the following steps: S1, Provides an oxide substrate; S2. Mix the nitrogen-containing organic precursor and the phosphorus-containing compound to obtain the precursor slurry; S3. The precursor slurry is loaded onto the surface of the oxide substrate and heat-treated in an oxygen-containing atmosphere to obtain the integral photocatalytic plate.
[0023] This invention employs an in-situ thermal polymerization method assisted by nitrogen-containing organic precursors and phosphorus-containing compounds to prepare an integral photocatalytic plate. During the heat treatment process, the phosphorus-containing compound first reacts with the hydroxyl groups on the surface of the oxide substrate to generate an MOP structure. Subsequently, the polymerized carbon nitride and phosphorus oxygen structure further form a covalently bridging structure at the MOPN interface, thereby achieving chemical bonding between the photocatalytic layer and the inorganic substrate. This avoids problems such as agglomeration, uneven dispersion, and poor contact with the substrate that may occur during the subsequent loading process of the pre-synthesized catalyst.
[0024] As a preferred embodiment of the preparation method of the present invention, the oxide substrate further includes a pretreatment step before use; the pretreatment includes ultrasonically cleaning the oxide substrate in deionized water and an organic solvent in sequence, and then drying it.
[0025] Preferably, the ultrasonic cleaning time is 10 min to 30 min.
[0026] In a preferred embodiment of the preparation method of the present invention, the precursor slurry further includes a solvent; the solvent includes at least one of deionized water, ethanol, and isopropanol.
[0027] Preferably, the solvent includes deionized water.
[0028] In a preferred embodiment of the preparation method described in this invention, the loading method is any one of coating, impregnation, or spraying.
[0029] In a preferred embodiment of the preparation method described in this invention, the loading amount of the precursor slurry on the surface of the oxide substrate is 0.1 g / cm³. 2 ~0.2g / cm 2 .
[0030] Preferably, the loading of the precursor slurry on the oxide substrate surface is 0.16 g / cm³. 2 .
[0031] In a preferred embodiment of the preparation method described in this invention, the heating rate of the heat treatment is 1℃ / min to 10℃ / min, the temperature is 450℃ to 600℃, and the time is 2h to 6h.
[0032] Preferably, the heating rate of the heat treatment is 5℃ / min, the temperature is 500℃, and the time is 3h.
[0033] As a preferred embodiment of the preparation method of the present invention, the heat treatment is followed by a post-treatment step; the post-treatment includes polishing the surface of the integral photocatalytic plate.
[0034] Thirdly, the present invention provides a photocatalytic reaction system, including the aforementioned integral photocatalytic plate.
[0035] As a preferred embodiment of the photocatalytic reaction system of the present invention, the photocatalytic reaction system includes a reactor shell, a light source system, a liquid inlet, a liquid outlet, a gas inlet, a gas outlet, a photocatalytic plate array disposed inside the reactor shell, and a fluid driving device for driving the reaction liquid to flow through the photocatalytic plate array. The photocatalytic plate array includes at least one of the integral photocatalytic plates.
[0036] The photocatalytic reaction system of the present invention can improve light energy utilization and hydrogen peroxide yield by increasing the number of photocatalytic plates and the effective reaction area. Furthermore, through array arrangement and fluid channel design, the continuous flow photocatalytic reaction system constructed by the present invention has the characteristics of high mass transfer efficiency, high light utilization efficiency and easy scale-up, and is suitable for continuous photocatalytic preparation of hydrogen peroxide, water treatment and other mobile phase photocatalytic reaction processes.
[0037] Preferably, the light source system is any one of LED light source, xenon lamp light source, mercury lamp light source, and solar simulator.
[0038] Preferably, the light source system is located above or to the side of the reactor shell.
[0039] Preferably, the arrangement of the photocatalytic plate array is any one of the following: array form, parallel plate form, corrugated plate form, honeycomb form, and multi-layer stacked form, and a fluid reaction channel is formed between adjacent integral photocatalytic plates.
[0040] More preferably, the spacing between adjacent integral photocatalyst plates is 1mm to 20mm.
[0041] Preferably, the fluid drive device is a peristaltic pump or a circulating pump.
[0042] Preferably, the flow rate of the fluid drive device is 10 mL / min to 500 mL / min.
[0043] More preferably, the flow rate of the fluid drive device is 50 mL / min to 200 mL / min.
[0044] More preferably, the flow rate of the fluid drive device is 100 mL / min.
[0045] Fourthly, the present invention provides the application of the integral photocatalytic plate and the photocatalytic reaction system in the photocatalytic preparation of hydrogen peroxide, the photocatalytic degradation of organic pollutants, and the photocatalytic antibacterial disinfection.
[0046] Compared with existing technologies, the beneficial effects of this invention are as follows: First, by constructing a MOPN interface covalent bridging structure between the oxide substrate and the carbon nitride photocatalytic layer, this invention achieves chemical bonding and firm anchoring of the catalytic layer on the substrate surface. Compared with existing physical coating or adhesive fixation methods, this covalently bonded interface has higher bonding strength and excellent resistance to fluid erosion. Under ultrasonic treatment and long-term liquid flow impact conditions, the catalytic layer is not easily detached, significantly improving the structural stability and service life of the material. Second, by introducing phosphorus doping, this invention effectively modulates the electronic band structure of carbon nitride, enhancing its absorption capacity for visible light, while promoting the efficient separation and interface migration of photogenerated electron-hole pairs. This significantly improves the quantum efficiency and surface catalytic reaction activity. Furthermore, the photocatalytic system of this invention can simultaneously utilize photogenerated electrons to drive the two-electron reduction reaction of dissolved oxygen and utilize photogenerated holes to drive the oxidation reaction of water molecules to generate hydrogen peroxide. Through the synergistic effect of the two reaction pathways, the overall generation efficiency of hydrogen peroxide is further improved. Furthermore, the photocatalytic structure formed by this invention is an integral component, which can be directly used as a fixed photocatalytic module in a reactor, eliminating the need for complex separation and recovery processes such as centrifugation and filtration. This significantly simplifies the post-reaction processing flow. Moreover, this integral photocatalytic plate is suitable for constructing continuous mobile phase photocatalytic reaction systems, enabling long-term continuous and stable operation of the photocatalytic reaction. It exhibits excellent reusability and engineering scale-up potential, which is beneficial for promoting the practical application of photocatalytic technology in large-scale production. In addition, the integral photocatalytic plate provided by this invention is not only suitable for the photocatalytic preparation of hydrogen peroxide, but can also be extended to the photocatalytic degradation of organic pollutants and the antibacterial and disinfection treatment of microorganisms, demonstrating multifunctional and integrated application advantages. It has significant application value in environmental remediation, chemical synthesis, and public health fields. Attached Figure Description
[0047] Figure 1 This is a schematic diagram of the preparation process of the integral photocatalytic plate in Embodiment 1 of the present invention; Figure 2 This is a schematic diagram illustrating the formation process of the Al-OPN interface covalent bridging structure on the alumina substrate surface in the integral photocatalytic plate of Embodiment 1 of the present invention; Figure 3 This is a high-resolution X-ray photoelectron spectroscopy (XPS) spectrum of the monolithic photocatalytic plate in Test Example 1 of the present invention; Figure 4 These are digital photographs of different integral photocatalyst plates before and after ultrasonic treatment in Test Example 2 of this invention; Figure 5 This is a schematic diagram of the photocatalytic reaction system in Application Example 1 of the present invention; Figure 6This is a comparison chart of hydrogen peroxide production rates in different photocatalytic reaction systems in Test Example 3 of the present invention; Figure 7 This is a bar chart comparing the remaining mass of the catalyst layer and the catalyst layer retention rate of the photocatalytic reaction system in Test Example 4 of the present invention during the cyclic test; Figure 8 This is a schematic diagram of the photocatalytic degradation of methylene blue (MB) by the photocatalytic reaction system in Test Example 5 of the present invention; Figure 9 This is a pseudo-first-order kinetic fitting curve of the photocatalytic reaction system for the photocatalytic degradation of methylene blue (MB) in Test Example 5 of the present invention; Figure 10 The image shows the UV-Vis absorption spectrum of the photocatalytic reaction system for Escherichia coli suspension in Test Example 6 of this invention. Detailed Implementation
[0048] To better illustrate the objectives, technical solutions, and advantages of this invention, the invention will be further described below with reference to specific embodiments. Those skilled in the art should understand that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0049] The following description, in conjunction with specific embodiments, illustrates the practical effects of the present invention.
[0050] Unless otherwise specified, the experimental methods used in the examples are conventional methods; the materials, reagents, equipment, etc. used are all commercially available unless otherwise specified.
[0051] Example 1: This embodiment provides an integral photocatalytic plate, the preparation process of which is shown in the schematic diagram below. Figure 1 As shown, using alumina ceramic sheets as a substrate, melamine as a nitrogen-containing organic precursor, and phosphoric acid as an interfacial bonding promoter, a carbon nitride catalyst layer is grown in situ on the substrate surface through a high-temperature polymerization reaction, forming a chemically bonded interface. The specific preparation method includes the following steps: (1) Substrate pretreatment Alumina ceramic sheets with dimensions of 5cm×5cm×0.1cm were selected as the substrate and ultrasonically cleaned in deionized water and anhydrous ethanol for 20 minutes in sequence to remove surface contaminants. The sheets were then dried for later use.
[0052] (2) Preparation of precursor slurry Weigh 4g of melamine and add it to 5mL of deionized water. Stir to form a uniform slurry. Then add phosphoric acid to adjust the molar ratio of phosphoric acid to melamine to 1.0:1. Continue stirring for 30min and then ultrasonically disperse for 30min to obtain a uniform precursor slurry.
[0053] (3) Precursor load The precursor slurry was uniformly coated onto the surface of a pretreated alumina ceramic substrate, with the loading of the precursor slurry controlled at 0.16 g / cm³. 2 This ensures that the precursor completely and uniformly covers the substrate.
[0054] (4) In-situ growth under heat treatment The substrate of the loaded precursor was placed in a tube furnace and heated to 500°C at a heating rate of 5°C / min in an air atmosphere, and held at that temperature for 3 hours.
[0055] like Figure 2 As shown, during the heat treatment process, melamine undergoes a thermal condensation reaction to form a carbon nitride layer; simultaneously, phosphoric acid undergoes a dehydration condensation reaction with the hydroxyl groups (-OH) on the surface of the alumina substrate to first form an Al-OP structure. This structure further forms an Al-OPN interfacial covalent bridge structure with nitrogen atoms in the carbon nitride, thereby achieving chemical bonding and firm anchoring between the catalyst layer and the substrate.
[0056] (5) Post-processing After naturally cooling to room temperature, the surface is lightly polished to obtain a smooth, monolithic photocatalytic plate, denoted as P. 1.0 @CN-AS, in the obtained monolithic photocatalytic plate, the carbon nitride layer is firmly fixed to the substrate surface through interfacial covalent bonds.
[0057] Example 2: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (2), the molar ratio of phosphoric acid to melamine is 1.2:1; The remaining steps and parameters are exactly the same as in Example 1.
[0058] Example 3: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (2), the molar ratio of phosphoric acid to melamine is 0.8:1; The remaining steps and parameters are exactly the same as in Example 1.
[0059] Example 4: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (2), melamine is replaced with an equal amount of dicyandiamide; The remaining steps and parameters are exactly the same as in Example 1.
[0060] Example 5: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (2), melamine is replaced with an equal amount of thiourea; The remaining steps and parameters are exactly the same as in Example 1.
[0061] Example 6: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (1), the alumina ceramic sheet is replaced with a titanium dioxide ceramic sheet of the same size; The remaining steps and parameters are exactly the same as in Example 1.
[0062] In the in-situ growth process of this embodiment, melamine undergoes a thermal polycondensation reaction to form a carbon nitride layer. Simultaneously, phosphoric acid reacts with the hydroxyl groups in the titanium dioxide substrate to first form a Ti-OP structure. This structure further forms a Ti-OPN interfacial covalent bridge structure with nitrogen atoms in the carbon nitride, thereby achieving chemical bonding and firm anchoring between the catalyst layer and the substrate.
[0063] Example 7: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (1), the alumina ceramic sheet is replaced with a silica ceramic sheet of the same size; The remaining steps and parameters are exactly the same as in Example 1.
[0064] In the in-situ growth of the heat treatment in this embodiment, melamine undergoes a thermal condensation reaction to form a carbon nitride layer. At the same time, phosphoric acid reacts with the hydroxyl groups in the silicon dioxide substrate to first form a Si-OP structure. This structure further forms a Si-OPN interface covalent bridging structure with the nitrogen atoms in the carbon nitride, thereby achieving chemical bonding and firm anchoring between the catalyst layer and the substrate.
[0065] Example 8: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (1), the alumina ceramic sheet is replaced with a zirconia ceramic sheet of the same size; The remaining steps and parameters are exactly the same as in Example 1.
[0066] In the in-situ growth process of this embodiment, melamine undergoes a thermal condensation reaction to form a carbon nitride layer. Simultaneously, phosphoric acid reacts with hydroxyl groups or oxygen bridges in the zirconium oxide substrate to first form a Zr-OP structure. This structure further forms a Zr-OPN interfacial covalent bridge structure with nitrogen atoms in the carbon nitride, thereby achieving chemical bonding and firm anchoring between the catalyst layer and the substrate.
[0067] Example 9: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (1), the alumina ceramic sheet is replaced with FTO conductive glass of the same size; The remaining steps and parameters are exactly the same as in Example 1.
[0068] In the in-situ growth of the heat treatment in this embodiment, melamine undergoes a thermal polycondensation reaction to form a carbon nitride layer. At the same time, phosphoric acid reacts with the hydroxyl groups in the FTO conductive glass substrate (the main components are fluorine-doped tin oxide and silicon dioxide) to first form a Sn-OP structure. This structure further forms a Sn-OPN interface covalent bridging structure with the nitrogen atoms in the carbon nitride, thereby achieving chemical bonding and firm anchoring between the catalyst layer and the substrate.
[0069] Example 10: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (1), the alumina ceramic sheet is replaced with alumina porous ceramic of the same size; The remaining steps and parameters are exactly the same as in Example 1.
[0070] Example 11: This embodiment provides an integral photocatalytic plate, the only difference between its preparation method and that of Embodiment 1 is: In step (1), the alumina ceramic sheet is replaced with an alumina honeycomb ceramic of the same size; The remaining steps and parameters are exactly the same as in Example 1.
[0071] Comparative Example 1: This comparative example provides an integral photocatalytic plate, the only difference between its preparation method and that of Example 1 is: In step (2), only melamine is used for thermal polymerization without adding phosphoric acid, and the resulting monolithic photocatalytic plate is denoted as CN-AS; The remaining steps and parameters are exactly the same as in Example 1.
[0072] Comparative Example 2: This comparative example provides an integral photocatalytic plate, the only difference between its preparation method and that of Example 1 is: In step (2), the molar ratio of phosphoric acid to melamine is 0.5:1, and the resulting monolithic photocatalytic plate is denoted as P. 0.5 @CN-AS; The remaining steps and parameters are exactly the same as in Example 1.
[0073] Comparative Example 3: This comparative example provides an integral photocatalytic plate, the only difference between its preparation method and that of Example 1 is: In step (2), the molar ratio of phosphoric acid to melamine is 1.5:1, and the resulting monolithic photocatalytic plate is denoted as P. 1.5 @CN-AS; The remaining steps and parameters are exactly the same as in Example 1.
[0074] Comparative Example 4: This comparative example provides an integral photocatalytic plate, the only difference between its preparation method and that of Example 1 is: In step (2), phosphoric acid is replaced with an equal amount of ammonium dihydrogen phosphate; The remaining steps and parameters are exactly the same as in Example 1.
[0075] Comparative Example 5: This comparative example provides an integral photocatalytic plate, the only difference between its preparation method and that of Example 1 is: In step (2), melamine is replaced with an equal amount of urea; The remaining steps and parameters are exactly the same as in Example 1.
[0076] Comparative Example 6: This comparative example provides an integral photocatalytic plate, the preparation method of which includes the following steps: (1) Substrate pretreatment Alumina ceramic sheets with dimensions of 5cm×5cm×0.1cm were selected as the substrate and ultrasonically cleaned in deionized water and anhydrous ethanol for 20 minutes in sequence to remove surface contaminants. They were then dried for later use.
[0077] (2) Preparation and coating of precursor powder Weigh 4g of melamine and place it in a corundum crucible. Heat the crucible to 500°C at 5°C / min in air atmosphere, keep it at the temperature for 3 hours, and grind it after natural cooling to obtain carbon nitride powder. The obtained carbon nitride powder was then mixed with a binder (which included E828 epoxy resin, polydimethylsiloxane (PDMS) and polyamide in a mass ratio of 10:1:3) at a mass ratio of 10:1. The mixture was then coated onto the surface of an alumina ceramic substrate and dried at 80°C. The surface was then lightly polished to obtain a smooth, integral photocatalytic plate.
[0078] Comparative Example 7: This comparative example provides an integral photocatalytic plate, the preparation method of which includes the following steps: (1) Substrate pretreatment Alumina ceramic sheets with dimensions of 5cm×5cm×0.1cm were selected as the substrate and ultrasonically cleaned in deionized water and anhydrous ethanol for 20 minutes in sequence to remove surface contaminants. They were then dried for later use.
[0079] (2) Preparation of precursor slurry Weigh 4g of melamine and place it in a corundum crucible. Heat the crucible to 500°C at 5°C / min in air atmosphere, keep it at the temperature for 3 hours, and grind it after natural cooling to obtain carbon nitride powder. The obtained carbon nitride powder was then mixed with phosphoric acid, and the molar ratio of phosphoric acid to melamine used in the preparation of carbon nitride was adjusted to 1.0:1. After stirring for 30 minutes, the mixture was ultrasonically dispersed for 30 minutes to obtain a uniform precursor slurry.
[0080] (3) Precursor load The precursor slurry was uniformly coated onto the surface of a pretreated alumina ceramic substrate, with the loading of the precursor slurry controlled at 0.16 g / cm³. 2 This ensures that the precursor completely and uniformly covers the substrate.
[0081] (4) Heat treatment The substrate of the loaded precursor was placed in a tube furnace and heated to 500°C at a heating rate of 5°C / min in an air atmosphere, and held at that temperature for 3 hours.
[0082] (5) Post-processing After naturally cooling to room temperature, the surface is lightly polished to obtain a smooth, integral photocatalytic plate.
[0083] Test Example 1: In this test case, the interfacial chemical structure of the monolithic photocatalytic plate of Example 1 was analyzed by X-ray photoelectron spectroscopy (XPS) to verify the formation of the Al-OPN interfacial covalent bridging structure.
[0084] like Figure 3 As shown, P in Embodiment 1 of the present invention 1.0 In the XPS high-resolution spectra of @CN-AS: In the Al2p spectrum, 74.20 eV corresponds to Al-O-Al, and 75.44 eV corresponds to Al-OP; in the O1s spectrum, 530.60 eV corresponds to Al-O, 531.77 eV corresponds to C=O, and 532.30 eV corresponds to Al-OP; in the P2p spectrum, 133.52 eV corresponds to PN, and 134.49 eV corresponds to OPN.
[0085] The XPS analysis results above fully demonstrate that in the monolithic photocatalytic plate of Example 1 of the present invention, phosphorus element is chemically bonded to both the alumina substrate and carbon nitride, forming a stable Al-OPN covalent bridging structure at the interface. This covalent bridging structure not only provides a strong anchoring effect for the catalytic layer, but also serves as an electron transport channel, which is conducive to the migration of photogenerated carriers at the interface between carbon nitride and the substrate, thus taking into account both structural stability and photocatalytic activity.
[0086] Test Example 2: This test example examines the structural stability and bonding strength of the monolithic photocatalytic plates prepared in Examples 1-11 and Comparative Examples 1-7 to evaluate the degree of bonding of the catalytic layer to the substrate surface.
[0087] Test method: After the sample was simply rinsed with deionized water and dried to constant weight, the catalyst growth mass of the sample was calculated (expressed as the difference between the total mass of the sample and the mass of the blank substrate). The sample was then placed in a beaker, and deionized water was added to completely immerse the sample. The sample was ultrasonically treated at a frequency of 40 kHz for 10 min. After ultrasonic treatment, the sample was removed and dried at 80 ℃ to constant weight. The catalyst layer retention rate was calculated by weighing the mass change before and after ultrasonic treatment (expressed as the percentage of the mass of the catalyst after ultrasonic treatment to the mass of the catalyst before ultrasonic treatment). At the same time, the turbidity of the ultrasonic treatment solution was observed to qualitatively evaluate the detachment of the catalyst layer.
[0088] Table 1: Test results of the bonding stability of the integral photocatalytic plate in Test Example 2 of the present invention As shown in Table 1 and Figure 4 As shown, the monolithic photocatalytic plate of Comparative Example 1 (CN-AS), without any added phosphorus-containing components, showed complete detachment of the catalyst layer after ultrasonic treatment, with a retention rate of 0%. Furthermore, obvious particle deposition was observed in the treatment solution, indicating that the catalyst layer and the substrate only had physical contact and no chemical bonding. The monolithic photocatalytic plates of Comparative Examples 4, 5, and 7 also failed to form a continuous and stable MOPN interface bridging structure, and the catalyst layer also completely detached after ultrasonic treatment (retention rate of 0% in all cases). The P in Comparative Example 2... 0.5 The @CN-AS sample, due to insufficient phosphoric acid addition, could not provide enough anchoring force, resulting in significant detachment of the catalyst layer and a retention rate of only 24.21%. Furthermore, the treated solution became noticeably turbid. (Comparative Example 3, P...) 1.5Although @CN-AS achieved a catalyst layer retention rate of over 99%, excessive phosphoric acid led to excessively high acidity in the precursor slurry, causing corrosion to the substrate surface during heat treatment. Furthermore, excessive phosphate ions occupied active sites of carbon nitride during the precursor thermal polycondensation, resulting in a significant decrease in subsequent photocatalytic activity. While Comparative Example 6 provided some physical fixation with the binder, the retention rate after ultrasonication was only 25.61%, and the treatment solution was noticeably turbid, indicating that physical adhesion was also insufficient to resist fluid erosion. In contrast, the P in Example 1 of this invention… 1.0 The surface of @CN-AS remained almost unchanged, the catalytic layer retention rate reached over 99%, and no obvious particle deposition was observed in the treatment solution. This indicates that the phosphoric acid ratio in the preparation method of this invention can effectively promote the formation of Al-OPN interface bonds, significantly improve the bonding strength between the catalytic layer and the substrate, and endow the photocatalytic plate with excellent mechanical stability and erosion resistance.
[0089] Application Example 1: This application example provides a continuous flow photocatalytic reaction system for the photocatalytic preparation of hydrogen peroxide, the structure of which is as follows: Figure 5 As shown; including: 1. Water inlet; 2. Water outlet; 3. Sealed reactor shell; 4. Exhaust port; 5. Air inlet; 6. Photocatalytic plate array; 7. Peristaltic pump; 8. Fluid reaction channel.
[0090] The sealed reactor shell is made of transparent and corrosion-resistant material, and a quartz light-transmitting cover is installed on the top to ensure that ultraviolet light, visible light or simulated sunlight can be transmitted into the reaction area; the quartz light-transmitting cover and the sealed reactor shell are connected by a sealing ring and fastening structure to form a closed reaction space. An array of photocatalytic plates is installed inside the reactor, which fixes nine integral photocatalytic plates from Example 1 in a 3×3 array structure inside the reactor, with adjacent photocatalytic plates arranged closely together without gaps. Figure 5 ); The reactor has an inlet at the bottom and an outlet at the top, which is connected to a peristaltic pump to achieve the circulation of the reaction liquid. The reactor has an air inlet and an exhaust outlet on its side for continuously supplying oxygen to provide reactants and maintain system pressure balance; The light source system uses a 300W xenon lamp, placed 100cm above the quartz light-transmitting cover plate, to simulate sunlight.
[0091] In this application embodiment, during operation of the continuous flow photocatalytic reaction system, the reaction liquid enters the reactor through the inlet and flows along the surface of the photocatalytic plate array under the drive of a peristaltic pump. Oxygen enters the reactor through the gas inlet and dissolves in the reaction liquid. Under the illumination of the light source system, the photocatalytic plate absorbs light energy to generate electron-hole pairs. The photogenerated electrons drive the oxygen to undergo a two-electron reduction reaction to produce hydrogen peroxide (O2 + 2H+).+ + 2e - →H2O2), while photogenerated holes promote the water oxidation reaction to generate hydrogen peroxide precursor active species, thereby realizing the continuous generation of hydrogen peroxide. The reacted liquid flows out through the outlet and can be returned to the storage device to form a circulating reaction system.
[0092] Application Examples 2-11: The only difference between the photocatalytic reaction systems in Application Examples 2-11 and Application Example 1 is that: The monolithic photocatalytic plate used in Example 1 was replaced with the monolithic photocatalytic plate used in Examples 2 to 11, respectively; The rest of the structure and operation are exactly the same as in Application Example 1.
[0093] Application Comparative Examples 1-7: The only difference between the photocatalytic reaction systems used in Comparative Examples 1-7 and those used in Example 1 is that: The monolithic photocatalytic plate used in Example 1 was replaced with the monolithic photocatalytic plates of Comparative Examples 1 to 7 respectively; The rest of the structure and operation are exactly the same as in Application Example 1.
[0094] Test Example 3: This test example demonstrates the performance of photocatalytic hydrogen peroxide production using the photocatalytic reaction systems of Application Examples 1-11 and Comparative Examples 1-7.
[0095] Test method: (1) Photocatalytic reaction Add 200 mL of deionized water to the reaction system as the reaction solution, and continuously introduce oxygen through the gas inlet, with the oxygen flow rate controlled at 100 mL / min. Turn on the peristaltic pump to circulate the reaction solution at a flow rate of 100 mL / min, allowing the reaction solution to flow along the fluid reaction channel across the surface of the photocatalytic plate array. The reaction time is 6 hours.
[0096] (2) The concentration of H2O2 in the reaction solution was determined by the titanium sulfate colorimetric method. Take 1 mL of the reaction solution and add it to 4 mL of titanium sulfate colorimetric solution. H2O2 can react with Ti(IV) to form a yellow titanium peroxide complex. Then, the absorbance at 405 nm is measured using a UV-Vis spectrophotometer. Finally, the concentration of H2O2 in the reaction solution is calculated using a pre-established H2O2 concentration-absorbance standard curve.
[0097] Samples were taken at 0h, 1h, 2h, 3h, 4h, 5h and 6h of the reaction, and the concentration of hydrogen peroxide was determined by the titanium sulfate colorimetric method. The cumulative amount of hydrogen peroxide (H2O2) produced, the hydrogen peroxide (H2O2) production rate (expressed as the amount of H2O2 produced per hour) and the hydrogen peroxide (H2O2) surface area production rate (expressed as the amount of H2O2 produced per square meter of photocatalytic plate per hour) were calculated.
[0098] Table 2: Performance test results of the photocatalytic hydrogen peroxide preparation system of Test Example 3 of the present invention As shown in Table 2 and Figure 6 As shown, the H2O2 production rate of the photocatalytic reaction system constructed by CN-AS in Comparative Example 1 is only 0.59 μmol·h. -1 This is because the carbon nitride layer in the sample without added phosphoric acid lacks chemical bonding with the substrate, resulting in poor interfacial contact and numerous interfacial defects encountered by photogenerated electrons during transport. Simultaneously, ultrasonic testing has confirmed the extensive shedding of the catalyst layer, leaving very little effective catalyst participating in the reaction. (Comparative Example 2 P) 0.5 The H2O2 production rate of the photocatalytic reaction system constructed by @CN-AS is only 15.03 μmol·h. -1 Although it showed some improvement compared to Comparative Example 1, the interfacial PN bridging structure was incomplete when the amount of phosphoric acid was insufficient, limiting the interfacial transport efficiency of photogenerated carriers. Furthermore, some of the catalyst layer gradually detached during the reaction, leading to a decrease in activity. Comparative Example 3 P 1.5 The H2O2 production rate of the photocatalytic reaction system constructed by @CN-AS is only 5.58 μmol·h. -1 Although its catalytic layer is firmly bonded (ultrasonic retention rate >99%), excessive phosphoric acid causes phosphate ions to occupy amino sites in the carbon nitride framework, disrupting the conjugated π-electron structure of carbon nitride and reducing light absorption capacity. Furthermore, excessive phosphorus forms an excessively thick POP oligomer layer at the interface, increasing interfacial resistance and hindering the directional transport of photogenerated electrons from carbon nitride to the substrate. The H2O2 production rate of the photocatalytic reaction system constructed in Comparative Example 4 is zero, because ammonium dihydrogen phosphate failed to effectively form a bond with the substrate and carbon nitride precursor during pyrolysis. In the simultaneous condensation reaction, the catalyst layer could not be stably anchored on the substrate surface, and most of the precursors escaped in gaseous form during heat treatment, resulting in extremely uneven coverage of the catalyst layer on the substrate surface. Comparative Example 5 also exhibited an extremely low H2O2 production rate, which is attributed to the disordered arrangement and low conjugation degree of the heptaazine ring units in the carbon nitride polymer structure generated by urea thermal condensation, and its weak interaction with phosphorus-containing species, making it difficult to form efficient charge migration channels. The H2O2 production rate of the photocatalytic reaction system constructed in Comparative Example 6 was only 2.32 μmol·h. -1Although the initial catalyst loading was high, the binder covered most of the active sites on the carbon nitride surface. The H2O2 production rate of Comparative Example 7 was also zero, indicating that even with the introduction of phosphoric acid, since the carbon nitride framework was completely solidified before mixing, the phosphoric acid could not form PN bonds with the N atoms in the framework, nor could it establish an effective MOP bridge with the substrate surface. It could only form a physical mixing layer, which quickly fell off during the reaction.
[0099] In contrast, Embodiment 1 P of the present invention 1.0 The H2O2 production rate of the photocatalytic reaction system constructed by @CN-AS reached 46.53 μmol·h. -1 The monolithic photocatalytic plate exhibits superior photocatalytic hydrogen peroxide production performance. This indicates that the Al-OPN interface structure formed by the phosphoric acid-assisted in-situ growth of the monolithic photocatalytic plate of this invention, on the one hand, firmly anchors the carbon nitride catalyst layer, ensuring long-term operational stability; on the other hand, this interface covalent bridging structure, acting as an atomic-scale electron transport channel, significantly reduces the interface barrier for photogenerated electrons migrating from carbon nitride to the substrate, promoting effective separation of photogenerated carriers and extending the lifetime of photogenerated electrons. This, in turn, significantly improves the selectivity and reaction rate of oxygen reduction to hydrogen peroxide. Conversely, without phosphoric acid, without in-situ growth, or without the formation of an interface bridging structure, the catalyst layer is prone to detachment and the photocatalytic performance significantly decreases. Furthermore, the Al-OPN interface structure formed by the phosphoric acid-assisted in-situ growth of the monolithic photocatalytic plate of this invention... 1.0 The hydrogen peroxide production rate of @CN-AS, after conversion, is 2066.68 μmol·h⁻¹. -1 ·m -2 The results were significantly higher than those of other comparative samples, which further demonstrates that the appropriate interfacial phosphorus bridging structure of the present invention can effectively promote the separation of photogenerated carriers and oxygen reduction reaction, while achieving high mechanical stability and high catalytic activity.
[0100] Test Example 4: This test example demonstrates the cyclic stability test of the photocatalytic reaction system in Application Example 1.
[0101] Test method: The photocatalytic preparation of hydrogen peroxide was carried out according to the method in Test Example 3. After each 6-hour photocatalytic reaction, the photocatalytic plate was removed from the reactor, rinsed with deionized water and dried naturally. The remaining mass of the catalyst layer was weighed and measured before the next round of reaction was carried out. A total of 10 cycles of testing were conducted.
[0102] The following control group was also set up: Centrifugal recovery group: After each round of reaction, the catalyst is recovered by centrifugation and redispersed in fresh reaction solution; Vacuum filtration unit: After each round of reaction, the catalyst is recovered through vacuum filtration and redispersed in fresh reaction solution.
[0103] Test results are as follows Figure 7 As shown, in Embodiment 1 P of the present invention 1.0 The photocatalytic reaction system constructed using @CN-AS maintained a catalyst layer mass of approximately 0.84–0.86 g after 10 cycles, with a mass retention rate greater than 99%, and no significant shedding was observed. The hydrogen peroxide production rate also did not show a significant decrease. In contrast, the centrifugal recovery group retained only about 40% of the catalyst mass after 10 cycles, and due to the inevitable loss and agglomeration of ultrafine carbon nitride powder during centrifugation, the catalytic activity declined significantly with each cycle. The vacuum filtration group had almost completely lost its catalyst after the fourth cycle, failing to maintain an effective catalytic reaction. This indicates that the Al-OPN interfacial covalent bonds constructed in this invention can significantly improve the bonding strength between the catalyst layer and the substrate, enabling the photocatalytic plate to maintain excellent stability and reusability under long-term continuous flow operation conditions, meeting the needs of engineering applications and solving the common industry problem of traditional powder catalysts being difficult to recover and easily lost in continuous flow reactions.
[0104] Test Example 5: This test case is used to verify the application effect of the photocatalytic reaction system of Example 1 of the present invention in the degradation of organic pollutants.
[0105] Test method: (1) Prepare 200 mL of methylene blue (MB) solution with a concentration of 10 mg / L as simulated organic wastewater. Then add the methylene blue solution to the photocatalytic reaction system and circulate it in the dark for 30 min at a flow rate of 100 mL / min to make the methylene blue and the photocatalytic plate reach adsorption-desorption equilibrium.
[0106] (2) Then turn on the 300W xenon lamp for irradiation. The distance of the light source is 100cm, and the flow rate is maintained at 100mL / min during the irradiation process.
[0107] Samples were taken and tested every 5 minutes. The absorbance at 664 nm was measured using a UV-Vis spectrophotometer. The total reaction time was 30 minutes. Finally, the degradation rate of methylene blue was calculated based on the change in absorbance.
[0108] like Figure 8 As shown, in Embodiment 1 P of the present invention 1.0 The photocatalytic reaction system constructed by @CN-AS, under 300W xenon lamp irradiation, showed a continuous decreasing trend in MB concentration with increasing irradiation time, and the solution color gradually lightened from the initial deep blue. After 30 minutes, the residual MB concentration (C) decreased. t / C0) as low as 0.0148 mg·L -1 This indicates that the integral photocatalytic plate of the present invention can efficiently drive the degradation process of organic pollutants in a continuous flow reactor; simultaneously, as Figure 9As shown, the MB degradation process conforms to a pseudo-first-order reaction kinetic model, with an apparent reaction rate constant k of 0.099 min. -1 (Use the formula ln(C0 / C)) t )=k t This further demonstrates that the monolithic photocatalyst of this invention possesses both high-efficiency reaction kinetics and operational stability in continuous flow environment remediation systems, and shows broad engineering application prospects in fields such as deep treatment of industrial wastewater, decolorization of dyeing and printing wastewater, and removal of emerging organic micropollutants.
[0109] Test Example 6: This test case is used to verify the application effect of the photocatalytic reaction system in Application Example 1 in antibacterial treatment.
[0110] Test method: (1) Preparation of bacterial culture Using *Escherichia coli* (ATCC 25922) as the model strain, beef extract peptone medium was prepared, sterilized at 121℃ for 20 min, inoculated with *E. coli*, and cultured at 37℃ and 180 rpm for 24 h. OD was measured using a UV-Vis spectrophotometer. 600 The bacterial concentration is approximately 1×10⁻⁶. 8 CFU / mL, then diluted with sterile culture medium for later use.
[0111] (2) Antibacterial test Add 200 mL of bacterial suspension to the reactor as the reaction solution. Use a 300 W xenon lamp as the light source to simulate sunlight irradiation. Maintain the distance of the light source at 100 cm. Turn on the peristaltic pump and set the flow rate to 100 mL / min. React continuously for 2 hours. The following control group was also set up: Control group: Experiments were conducted under the same conditions using a reactor without a photocatalytic plate; Using OD 600 The bacterial cell concentration before and after the reaction was determined by a method based on a pre-established OD value. 600 - Convert the bacterial concentration using the CFU standard curve and calculate the antibacterial rate.
[0112] like Figure 10 As shown, in Embodiment 1 P of the present invention 1.0 After the photocatalytic reaction system constructed by @CN-AS was continuously operated for 2 hours under simulated sunlight irradiation by a 300 W xenon lamp, the concentration of colony-forming units (CFU) of Escherichia coli in the reaction system increased to 1.03 × 10⁻⁶. 8 CFU / mL, lower than the blank group (1.71×10⁻⁶). 8The photocatalytic plate (CFU / mL) exhibits an antibacterial rate of 95.77%, demonstrating excellent ability to inhibit the growth of Escherichia coli. This result indicates that the integral photocatalytic plate of the present invention is not only suitable for the photocatalytic degradation of chemical pollutants, but also plays an important role in public health fields such as water disinfection, sterilization of medical device surfaces, and air purification. Its integral configuration avoids the residual risk of powder catalysts in antibacterial applications and has good biosafety.
[0113] In summary, this invention provides an integral photocatalytic plate, its preparation method, and its application. Through a phosphoric acid-assisted in-situ thermal polymerization strategy, a MOPN (M = Al, Ti, Si, Zr, Sn, etc.) interfacial covalent bridging structure was successfully constructed on the surface of an oxide substrate, achieving a firm anchoring of the carbon nitride catalyst layer on the substrate. This not only endows the catalyst layer with excellent anti-detachment properties (retention rate >99% after ultrasonic treatment) but also effectively promotes the interfacial separation and migration of photogenerated carriers as an electron transport channel, enabling a photocatalytic hydrogen peroxide production rate of 2066.68 μmol·h⁻¹. -1 ·m -2 Furthermore, the integral photocatalytic plate of this invention also exhibits excellent performance in the degradation of organic pollutants and antibacterial properties. After 10 cycles of testing, the mass retention rate of the catalyst layer is still greater than 99%, demonstrating excellent long-term operational stability. It improves upon the problems of easy agglomeration, difficult recovery, and large pressure drop of traditional powder catalysts during application. It has broad application prospects and engineering promotion value in the fields of photocatalytic synthesis of high-value chemicals, wastewater treatment, air purification, and antibacterial disinfection.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. An integral photocatalytic plate, characterized in that, It includes an oxide substrate and a carbon nitride catalyst layer formed on the surface of the oxide substrate; The carbon nitride catalyst layer is connected to the oxide substrate through a MOPN interface covalent bridging structure, wherein M includes at least one of B, Sn, Al, Zr, Mg, Ti, and Si; The carbon nitride catalyst layer is formed by in-situ thermal polycondensation of nitrogen-containing organic precursors and phosphorus-containing compounds. The molar ratio of the nitrogen-containing organic precursor to the phosphorus-containing compound is (0.8~1.2):
1.
2. The integral photocatalytic plate as described in claim 1, characterized in that, The oxide substrate is any one of alumina ceramic sheet, titanium dioxide ceramic sheet, silicon dioxide ceramic sheet, zirconia ceramic sheet, FTO conductive glass, alumina porous ceramic, and alumina honeycomb ceramic.
3. The integral photocatalytic plate as described in claim 1, characterized in that, In the MOPN interface covalent bridging structure, the P atom serves as the bridging center, with one end chemically bonded to the oxide substrate surface via MOP bonds and the other end chemically bonded to the carbon nitride catalyst layer via PN bonds.
4. The integral photocatalytic plate as described in claim 1, characterized in that, The nitrogen-containing organic precursor includes at least one of melamine, dicyandiamide, and thiourea.
5. The integral photocatalytic plate as described in claim 1, characterized in that, The phosphorus-containing compound includes at least one of phosphoric acid, phosphate, and organophosphorus compounds.
6. A method for preparing the integral photocatalytic plate according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1, Provides an oxide substrate; S2. Mix the nitrogen-containing organic precursor and the phosphorus-containing compound to obtain the precursor slurry; S3. The precursor slurry is loaded onto the surface of the oxide substrate and heat-treated in an oxygen-containing atmosphere to obtain the integral photocatalytic plate.
7. The preparation method according to claim 6, characterized in that, The heating rate of the heat treatment is 1℃ / min to 10℃ / min, the temperature is 450℃ to 600℃, and the time is 2h to 6h.
8. A photocatalytic reaction system, characterized in that, Includes the integral photocatalytic plate as described in any one of claims 1 to 5.
9. The photocatalytic reaction system as described in claim 8, characterized in that, The photocatalytic reaction system includes a reactor shell, a light source system, a liquid inlet, a liquid outlet, an air inlet, an exhaust outlet, a photocatalytic plate array disposed inside the reactor shell, and a fluid drive device for driving the reaction liquid to flow through the photocatalytic plate array. The photocatalytic plate array includes at least one of the integral photocatalytic plates.
10. The application of the integral photocatalytic plate according to any one of claims 1 to 5 and the photocatalytic reaction system according to any one of claims 8 to 9 in the photocatalytic preparation of hydrogen peroxide, the photocatalytic degradation of organic pollutants, and the photocatalytic antibacterial disinfection.
